The mutant p53‐ID4 complex controls VEGFA isoforms by recruiting lncRNA MALAT1. (26th June 2017) - Pruszko, Magdalena; Milano, Elisa; Forcato, Mattia; Donzelli, Sara; Ganci, Federica; Di Agostino, Silvia; De Panfilis, Simone; Fazi, Francesco; Bates, David O; Bicciato, Silvio; Zylicz, Maciej; Zylicz, Alicja; et al.
Abstract: The abundant, nuclear‐retained, metastasis‐associated lung adenocarcinoma transcript 1 (MALAT1) has been associated with a poorly differentiated and aggressive phenotype of mammary carcinomas. This long non‐coding RNA (lncRNA) localizes to nuclear speckles, where it interacts with a subset of splicing factors and modulates their activity. In this study, we demonstrate that oncogenic splicing factor SRSF1 bridges MALAT1 to mutant p53 and ID4 proteins in breast cancer cells. Mutant p53 and ID4 delocalize MALAT1 from nuclear speckles and favor its association with chromatin. This enables aberrant recruitment of MALAT1 on VEGFA pre‐mRNA and modulation of VEGFA isoforms expression. Interestingly, VEGFA‐dependent expression signatures associate with ID4 expression specifically in basal‐like breast cancers carrying TP53 mutations. Our results highlight a key role for MALAT1 in control of VEGFA isoforms expression in breast cancer cells expressing gain‐of‐function mutant p53 and ID4 proteins. Synopsis: The oncogenic lncRNA MALAT1 controls alternative splicing by modulating the distribution of splicing factors. This study describes a MALAT1‐containing ribonucleoprotein complex, which promotes the expression of pro‐angiogenic VEGFA isoforms in breast cancer. Oncogenic splicing factor SRSF1 bridges lncRNA MALAT1 to mutant P53 and ID4 in breast cancer. Mutant P53 and ID4 stabilize the interaction of SRSF1 with lncRNA MALAT1. Mutant P53 and ID4 favor the association of MALAT1 with chromatin. Recruitment of MALAT1 to VEGFA pre‐mRNA promotes the production of pro‐angiogenic isoforms. Abstract : The oncogenic lncRNA MALAT1 controls alternative splicing by modulating the distribution of splicing factors. This study describes a MALAT1‐containing ribonucleoprotein complex, which promotes the expression of pro‐angiogenic VEGFA isoforms in breast cancer.